ACUTE COMPLICATIONS OF DIABETES MELLITUS: CLINICAL CHARACTERISTICS AND OPTIMIZATION OF EMERGENCY MANAGEMENT - Kobilov , Alimardan (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Acute complications of diabetes mellitus, including diabetic ketoacidosis, hyperosmolar hyperglycemic state, and severe hypoglycemia, represent critical endocrinological emergencies associated with a high risk of adverse clinical outcomes. This study focuses on evaluating the clinical structure, underlying mechanisms, and primary precipitating factors of these acute conditions to optimize therapeutic strategies in intensive care settings. A comprehensive clinical analysis revealed that diabetic ketoacidosis remains the most prevalent acute complication, predominantly triggered by poor adherence to insulin therapy and the presence of concomitant infectious diseases. Additionally, occurrences of severe hypoglycemia were frequently linked to irrational dosing regimens and compromised renal clearance of hypoglycemic agents due to progressive diabetic nephropathy. The findings strongly indicate that the implementation of standardized, protocol-driven emergency interventions—emphasizing cautious fluid resuscitation and continuous intravenous insulin therapy—significantly accelerates metabolic stabilization and reduces the duration of intensive care treatment. Ultimately, improving patient education regarding sick-day management and ensuring strict adherence to modern clinical protocols are paramount for preventing these life-threatening emergencies.